ANALISIS ETIKA BERMEDIA SOSIAL MAHASISWA BERDASARKAN NILAI-NILAI PANCASILA DI FAKULTAS ILMU PENDIDIKAN UNIMED - Evika Kartika Sari Lawolo; Destri Natalia Telaumbanua; Ebyghael Joito Nababan; Yandira Arizki Fatiha; Julia Ivanna (STKIP Subang, 2026)
This study aims to analyze the ethics of social media use among students based on Pancasila values at the Faculty of Education, Universitas Negeri Medan (UNIMED). The rapid development of digital technology has made social media an integral part of students’ daily lives, yet it also raises various ethical issues such as the spread of hoaxes, hate speech, and cyberbullying. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving 15 students selected through purposive sampling. The results indicate that students generally possess a basic understanding of social media ethics, including maintaining politeness, respecting others’ opinions, and avoiding misinformation. However, the implementation of Pancasila values in digital interactions is not yet consistent. Violations such as inappropriate language use, passive attitudes toward unethical behavior, and lack of information verification are still common. Low digital literacy is identified as a major contributing factor. Nevertheless, students recognize their role as agents of change in promoting ethical behavior online, although this role has not been optimally realized. Therefore, strengthening digital literacy and internalizing Pancasila values are essential to foster responsible, ethical, and character-based digital behavior among students.